Locked Anterior Hip Dislocation with Ipsilateral Greater Trochanteric Fracture and Common Femoral Artery Compression: A Rare Case Report - Didi Indra, Faris Indra Prahasta; Ching Eng , Bryan Teoh; Agud Salim , Nurul ‘Izzati (IIUM Medical Journal Malaysia, 2025)
We report a rare case of post-traumatic anterior hip dislocation with ipsilateral greater trochanteric fracture and compression of the common femoral artery. To our knowledge, this is the first report that highlights a rare pubic anterior dislocation with greater trochanter fracture complicated with a pale, pulseless limb. Additionally, after two unsuccessful closed manipulative reduction (CMR) attempts, an urgent open reduction was performed, which resulted in an immediate recovery of the distal circulation. We emphasize the need for urgent open reduction following failed CMR. A delayed open reduction that was carried out 12 hours after the injury may have contributed to the surgical site infection, avascular necrosis, and heterotopic ossification that developed in our case.